State‐wide prioritisation of vertebrate pest animals in Queensland, Australia. (16th February 2023) - Harriott, Lana; Amos, Matt; Brennan, Michael; Elsworth, Peter; Gentle, Matthew; Kennedy, Malcolm; Pople, Tony; Scanlan, Joe; Speed, James; Osunkoya, Olusegun O.
Abstract : Invasive organisms are key drivers of environmental change globally. Both native and non‐native species can become pests that require management or control. Vertebrate pest animals may cause a range of economic, environmental and social impacts for which various plans are developed at a local, state and national scale to aid their management. There are multiple vertebrate pest species in Australia which vary in the type and severity of their negative effects. Prioritisation of these pests and their impacts is critical for management to be cost‐effective. We accessed pest management plans (PMPs) from 66 (of 71) local government areas (LGAs) across the state of Queensland to collate a list of vertebrate pest species present in each LGA. Local government areas were then grouped into easily identifiable regions (Regional Organisation of Councils, 'ROC' regions, 10 in all) and vertebrate pest species lists were collated for each region. At regional workshops, each pest species was ranked as no, low, medium or high priority by stakeholders. Rankings were used to develop impact scores resulting in a priority list of vertebrate pest animal species at the state level. Fifty‐three species were identified in individual LGA PMPs of which 25 were considered priorities at the regional level. Most species prioritised at the state level were mammals, with Wild Dogs (including Dingoes; Canis familiaris ), Feral Pigs ( Sus scrofa ) and Feral Cats ( Felis catus ) being the three highest ranked. Similarities in priority species were evident across ROC regions, however, several regions prioritised pests specific to their location. The data supported a further amalgamation of the 10 ROC regions into five main groups based on the set of vertebrate pest species that were present. Prioritisation lists should be regularly updated as technologies develop, established pest animal impacts change and new species incursions occur.